2022
DOI: 10.1186/s12916-021-02219-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of heart failure with preserved ejection fraction helps risk stratification for hypertrophic cardiomyopathy

Abstract: Background Heart failure with preserved ejection fraction (HFpEF) is the dominant form of heart failure (HF). We here aimed to investigate the characteristics and prognosis of HFpEF in patients with hypertrophic cardiomyopathy (HCM). Methods This was a prospective cohort study and patients with HCM with available NT-proBNP results were enrolled. Patients were categorized into HFpEF [defined as LVEF ≥50%, with symptoms or signs of HF, and N-terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Moreover, patients with increased NT-proBNP levels were associated with an increased risk of cardiac death [ 29 , 30 ]. This suggests that I-LGE is a sign of advanced cardiomyopathy, which could explain the higher level of NT-proBNP than NI-LGE in HCM [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patients with increased NT-proBNP levels were associated with an increased risk of cardiac death [ 29 , 30 ]. This suggests that I-LGE is a sign of advanced cardiomyopathy, which could explain the higher level of NT-proBNP than NI-LGE in HCM [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the 2016 ESC guideline ( 30 ), the NT-proBNP cutoff value is 125 pg/mL, whereas the 2017 AHA criteria suggested using a threshold of 800 pg/mL ( 14 ). A study indicated that compared to the cut-off value of NT-proBNP of the ESC guideline, the AHA criteria are more conducive to risk stratification in HCM patients ( 31 ). Accordingly, in this study, we chose 800 pg/mL as the threshold criterion for the group.…”
Section: Discussionmentioning
confidence: 99%
“…180 Concomitant presence of both conditions is associated with a worse prognosis. 197 In patients with concomitant disease, general HFpEF treatment is advisable, in addition to treatment for hypertrophic cardiomyopathy. Briefly, in symptomatic patients, pharmaceutical treatment options include non-vasodilating beta-blockers, verapamil, disopyramide, and mavacamten.…”
Section: Hypertrophic Cardiomyopathymentioning
confidence: 99%
“…Obstructive hypertrophic cardiomyopathy causes HFpEF in most patients, and non‐obstructive hypertrophic cardiomyopathy causes HFpEF in ∼10% of patients 180 . Concomitant presence of both conditions is associated with a worse prognosis 197 . In patients with concomitant disease, general HFpEF treatment is advisable, in addition to treatment for hypertrophic cardiomyopathy.…”
Section: Secondary Heart Failure With Preserved Ejection Fractionmentioning
confidence: 99%